Analisis dan simulasi solusi kemacetan akibat pengaruh bus kota pada jalinan tunggal jalan arteri - Ratieh Rahmadhani Warto SA; Eva Azhra Latifa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
Jalan Transyogi has a interweaving that connects Jalan Buperta with the Cibubur Toll Exit. At this weaving section, vehicles tend to slow down, further compounded by the presence of bus stops on the shoulder of the road, leading to conflicts and congestion. This study aims to analyze the causes of congestion and propose solutions to alleviate it on Jalan Transyog. This research employs a quantitative method, where data is collected through surveys on traffic volume, vehicle types, and speeds during peak and non-peak hours on weekdays, as well as secondary data as supporting information. The data is analyzed using PKJI 2023 and subsequently simulated using the VISSIM in 3D. The results of the analysis show that the ratio of interweaving for the Jalan Transyogi section is 0.48, meaning the link is still feasible. Based on the results of the single line capacity analysis of the influence of the presence of city buses, the degree of saturation (DJ) value was 1.014; travel speed (VT) is 18.62 km/hours, and travel time (WT) is 42 seconds. Calculations reveal that the arrival of one bus causes an additional 41 instances of slowing vehicles due to side friction. These values decreased to a degree of saturation (DJ) of 0.677; travel speed (VT) 21 km/hours; and the average travel time (WT) required is 36 seconds, after the best alternative solution is implemented by eliminating side obstacles and adjusting the operating hours of medium vehicles (KS) so as not to pass through Jalan Transyogi at peak hours, as well as creating a special lane for city buses. This alternative solution can last for 1 year, namely until 2025, and requires a review in the second year to ensure the feasibility requirements for a interweaving on the Jalan Transyogi are still met.